The short-chain fatty acids and their role in the microbiota – gut – brain axis - Lyulya, Anastasiya S.; Fedorovich, Sergei V. (Experimental Biology and Biotechnology, 2024)
Disruption of the microbiota – gut – brain axis may contribute to the pathogenesis of various diseases of the central nervous system, such as Alzheimer’s disease, Parkinson’s disease, depression, autism spectrum disorders and etc. There are several way of communication between the gut and the brain. One of them is the synthesis of bacterial metabolites, which cause a directly influence brain cells. Key metabolites with such properties include short-chain fatty acids. They is synthesised by the microbiome primarily from dietary fiber. The main short-chain fatty acids in the microbiota – gut – brain axis are propionic and butyric acids. In general, it is believed that propionic acid has a mainly neurotoxic effect, and butyric acid is neuroprotective. But at the same time, such a division is rather conditional. Both compounds are able to penetrate the blood-brain barrier. Their concentration in cerebrospinal fluid and blood plasma, according to most studies, varies in the range of 2–20 µmol/L, but in some pathologies it can rise up to 5 mmol/L. The action of short-chain fatty acids on the cells in nervous system is mediated generally by specific G-protein coupled receptors and epigenetic mechanisms. However, it cannot be ruled out that other potential signaling pathways are involved in the action of short-chain fatty acids on neurons. Deciphering the mechanisms of neuron regulation by propionic and butyric acids provides possibility to identify new pharmacological targets for the treatment of various brain diseases.